The history of the semantic hacking project and the lessons it teaches for modern cognitive security - Thompson, Paul; Guillory, Sean (Frontiers in Artificial Intelligence, 2025)
The Semantic Hacking Project ran from 2001 to 2003. It focused on how information systems (and the human decisions shaped by them) could be exploited through attacks not on code or infrastructure, but on meaning. This work is relevant to contemporary cognitive security concerns in the face of today’s information space. The work provides insight into the key question of how people come to hold the beliefs which they do. The project anticipated many of today’s challenges (disinformation campaigns, social media manipulation, AI-generated narratives) not just in technical terms, but in philosophical and linguistic terms. At the heart of its concern was a simple but powerful question: What happens when you can manipulate the inputs to a person’s belief system without the person knowing it? This question has only grown more urgent in an era of generative AI, large language models (LLMs), and algorithmically amplified influence.